Development of a Conceptual Framework for the Study of Building Maintenance Operation Processes in the Context of Facility Management - Lee, H.; Scott, David (The Hong Kong Institute of Surveyors, 2008)
Building maintenance operation processes are not noticeable and not attractive. With the development of facility management, there are impacts on the building maintenance operation processes in terms of cost, quality and process. Top management at the strategic level always challenges operation process efficiency from the planning stage to implementation. On the other hand, maintenance personnel at the operational level must face the challenge of insufficient maintenance resources and lack of support from top management. These misalignments do not help the effectiveness of maintenance and operation. This paper is part of a research study focusing on the development of a conceptual framework among the main aspects in building maintenance from the strategic and operational perspectives. The discussions include arguments on the maintenance policy, challenges of strategic maintenance decisions, and impacts on the maintenance operations from the influences of facility management as well as performance management. The aim is to uncover the grounds for the development of research questions in identifying the gaps between the top management at the strategic level and maintenance personnel at the operational level for improving the efficiency of maintenance operation processes. Main research questions are developed based on established overall conceptual framework, which consists of investigation about development of building maintenance objectives, types of challenges of building maintenance strategy, impacts of building maintenance in the context of facility management and improvement of building maintenance operation processes.